Atomic and structural modifications of two-dimensional transition metal dichalcogenides for various advanced applications. Issue 26 (14th June 2022) - Kirubasankar, Balakrishnan; Won, Yo Seob; Adofo, Laud Anim; Choi, Soo Ho; Kim, Soo Min; Kim, Ki Kang
Abstract : Atomic and structural modification is an effective method for fine tuning the physical and chemical properties of 2D TMDs and their heterostructures, which enables various advanced applications. Abstract : Two-dimensional (2D) transition metal dichalcogenides (TMDs) and their heterostructures have attracted significant interest in both academia and industry because of their unusual physical and chemical properties. They offer numerous applications, such as electronic, optoelectronic, and spintronic devices, in addition to energy storage and conversion. Atomic and structural modifications of van der Waals layered materials are required to achieve unique and versatile properties for advanced applications. This review presents a discussion on the atomic-scale and structural modifications of 2D TMDs and their heterostructures via post-treatment. Atomic-scale modifications such as vacancy generation, substitutional doping, functionalization and repair of 2D TMDs and structural modifications including phase transitions and construction of heterostructures are discussed. Such modifications on the physical and chemical properties of 2D TMDs enable the development of various advanced applications including electronic and optoelectronic devices, sensing, catalysis, nanogenerators, and memory and neuromorphic devices. Finally, the challenges and prospects of various post-treatment techniques and related future advanced applications are addressed.